2008
DOI: 10.1029/2008gc002127
|View full text |Cite
|
Sign up to set email alerts
|

Tracking provenance change during the late Miocene in the eastern Mediterranean using geochemical and environmental magnetic parameters

Abstract: [1] Marls of the Metochia section (Gavdos, Greece) have been analyzed using geochemistry, environmental magnetism, and diffuse reflectance spectrometry to study late Miocene paleoenvironmental changes in the eastern Mediterranean region. Fuzzy c-means cluster analysis (FCM), combined with nonlinear mapping (NLM), has been performed on a multiparameter data set to identify and characterize terrigenous source areas from North Africa and the Aegean margin. The parameters included in the FCM were selected on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 72 publications
(110 reference statements)
2
20
0
Order By: Relevance
“…This fraction is large enough to include both pedogenic and lithogenic hematite grains, which can then reach the Eastern Mediterranean Sea as constituents of eolian dust. This is in agreement with the eolian origin that has been proposed for hematite in Eastern Mediterranean marine sediments by comparing HIRM data with proxies for Saharan dust supply, such as Ti/Al ratios (Larrasoaña et al, 2003a(Larrasoaña et al, , 2008Köhler et al, 2008;Liu et al, 2012b) (Figure 3).…”
Section: Discussion Origin Of Magnetic Minerals In Eastern Mediterransupporting
confidence: 74%
See 4 more Smart Citations
“…This fraction is large enough to include both pedogenic and lithogenic hematite grains, which can then reach the Eastern Mediterranean Sea as constituents of eolian dust. This is in agreement with the eolian origin that has been proposed for hematite in Eastern Mediterranean marine sediments by comparing HIRM data with proxies for Saharan dust supply, such as Ti/Al ratios (Larrasoaña et al, 2003a(Larrasoaña et al, , 2008Köhler et al, 2008;Liu et al, 2012b) (Figure 3).…”
Section: Discussion Origin Of Magnetic Minerals In Eastern Mediterransupporting
confidence: 74%
“…These values indicate subtle magnetite concentration variations in background sediments (Figure 3). Magnetic data indicate that hematite is also ubiquitous in Eastern Mediterranean Sea sediments (Kruiver and Passier, 2001;Larrasoaña et al, 2003bLarrasoaña et al, , 2006Larrasoaña et al, , 2008Balsam et al, 2007;Köhler et al, 2008), as has also been shown by diffuse reflectance spectroscopy (DRS) data (Heslop et al, 2007;Liu et al, 2012b). Hematite abundances are typically inferred using HIRM or other properties aimed at isolating high-coercivity mineral signals (e.g., an alternating field-demagnetized IRM or IRM@AF) (Larrasoaña et al, 2003b(Larrasoaña et al, , 2006(Larrasoaña et al, , 2008Liu et al, 2012b).…”
Section: Marine Sedimentsmentioning
confidence: 99%
See 3 more Smart Citations